Development of physical training program to boost functional strength in firefighter recruits using a modified nominal group technique - Rosnah Ismail,; Noor Dalila Inche Zainal Abidin,; Asnarulkhadi Abu Samah,; Nor Hisham Mohammad,; Abdul Khair Osman,; Ismail Abdul Ghani,; Ashrul Riezal Asbar, (Universiti Kebangsaan Malaysia, 2025)
A series of comprehensive focus group discussions with active firefighters revealed that inconsistencies in incorporating a rigorous physical training program during work hours contributed significantly to the challenges of maintaining functional fitness, particularly strength. This article outlines a process for identifying the specific exercises required to enhance strength, drawing on the expertise and experience of physical trainers. Modified nominal group technique (mNGT) sessions were conducted to identify and rank exercises for five functional strengths (i.e., pushing, pulling, lifting, carrying, and dragging). A total of six physical trainers from the firefighter academy were interviewed to 1) identify the skeletal muscles involved in the functional movements using a visual aid; 2) generate ideas for exercises via brainstorming; 3) privately rank the displayed list of exercises for each muscle group involved in each functional movement; and 4) design a physical training programme for beginner, intermediate and advanced levels by manipulating loads. Males dominated the expert group (66.7%) and had a mean of 11.50 (SD 5.20) years of experience in physical training. The mNGTs yielded three top-ranking exercises for each functional strength: 1) Pushing: the push-up, sit-up, and jumping jack; 2) pulling: the push-up, jumping jack, and sit-up; 3) lifting: the jumping jack, push-up, and jumping squat; 4) carrying: the push-up, plank, and sit-up; and 5) dragging: the jumping jack, sit-up, and jumping squat. Then each exercise was designed for the beginner, intermediate, and advanced levels by manipulating loads (i.e. additional weight or number of repetitions). This study demonstrated that mNGT is an effective tool for identifying the three top-ranking exercises that address firefighter recruits’ functional strength. The experts chose multi-joint exercises targeting agonist and antagonist skeletal muscle groups and mimicking movements of daily work life. The exercises, corroborated by previous empirical evidence, provide opportunities for common skeletal muscle groupings to be targeted simultaneously to increase cardiovascular adaptations over a shorter period. The physical exercise is now ready to be implemented for piloting purposes among firefighter recruits.